Budidaya Ikan Gurami (Ospheronemus Gouramy) dalam Kolam Bundar pada Kelompok Pemuda Sabilulungan di Sindangkasih Ciamis - Hetty Patmawati; Enok Sumarsih; Setya Wahyuningsih; Muhamad Zulfikar Mansyur; Rahmat Rahmat (Institut Pertanian Bogor, 2022)
This activity aims to improve the knowledge and skills of gourami cultivators in Sindangkasih Village, Sindangkasih District, Ciamis Regency, and to understand the benefits of circular ponds as technology in gourami cultivation to increase the quality and quantity of gourami production. The method of carrying out activities through several stages, namely: Preparation & coordination; Implementation; Monitoring and evaluation. The implementation stage begins by providing counselling regarding the cultivation of gourami in circular ponds, followed by the provision of circular ponds as another option for cultivation so that the cultivators do not experience many losses. As a result of the activity, the cultivators switched to circular ponds. Hence, water quality is more controlled, stocking density, more efficient and effective feeding, there are no dead spots in circular ponds so that fish is always moving. Dirt is not concentrated in one point and, pests can be tackled faster because water is controlled, and pests are quickly controlled, the mortality rate is low. As a result, the maximum yield of gourami fish is within four months. The circular ponds are different from conventional ponds, where water conditions are not optimally controlled so that pests cannot be predicted and are slow in pest management so that the mortality rate is high.